Agricultural managed aquifer recharge (Ag-MAR)—a method for sustainable groundwater management: A review. Issue 3 (1st February 2023) - Levintal, Elad; Kniffin, Maribeth L.; Ganot, Yonatan; Marwaha, Nisha; Murphy, Nicholas P.; Dahlke, Helen E.
Abstract: More than two billion people and 40% of global agricultural production depend upon unsustainable groundwater extraction. Managed aquifer recharge (MAR), the practice of strategically recharging water to replenish subsurface storage, is an important subbasin scale practice for managing groundwater more sustainably. However, it is not yet reaching its full potential to counterbalance growing global groundwater demand. Agricultural managed aquifer recharge (Ag-MAR) is an emerging method for spreading large volume flows on agricultural lands and has capacity for widespread global implementation. Yet, knowledge gaps, synergies, and tradeoffs in Ag-MAR research still exist. We identify six key system considerations when implementing Ag-MAR: water source, soil and unsaturated zone processes, impact on groundwater, crop system suitability, climate change and impact on greenhouse gas emissions, and social and economic feasibility. We describe the present distribution, need for common terminology, and benefits of Ag-MAR including groundwater storage, increased environmental flows, and domestic wells support. We then outline major gaps, namely, water quality impacts, and crop health and yield. We showcase the multidisciplinary approach needed for communication and coordination of Ag-MAR programs with stakeholders and the public and provide a framework for implementation. Finally, we outline a vision for the path to Ag-MAR implementation. Ag-MAR is an important approach for achieving groundwater sustainability. However, it is one of many necessary solutions and does not offset the need for groundwater conservation. Graphical abstract: UF0001